GET RID OF A LIFE OF SOMEONE IN PLANNED BY TEENAGERS (CRIMINOLOGY AND ISLAMIC LAW PERSPECTIVE) - Simatupang, Nursariani (Proceeding International Seminar of Islamic Studies, 2023)
The rapid development of technology has resulted in the emergence of various sites that not only discuss positive things, but also offer negative thing, namely the business of selling human organs. It is very easy accessed by teenagers, and inflicted crime on the teenagers. The form of crime committed by the teenager is to get rid of a life. This research is a normative juridical research, with data sources in the form of secondary data. Data collection techniques are documentation studies. Teenagers as the next generation of the nation should do their duty as students, study, read books, play, and fight for their good future. The ease of accessing negative sites results in children easily following what they read from the site and resulted in them falling into the crime of get rid of a life, even though these acts are prohibited in Islamic Law and are very detrimental to teenagers. The crime was committed by teenagers because they were tempted by a very high offer for the sale of human organs of 80,000 dollars, and were supported by the difficult economic conditions of his family.  Negatively charged sites must be stopped, to prevent teenagers from committing crimes.